Study of Certain Biomarkers in Iraqi Female Patients with Breast Cancer (Baghdad Science Journal, 2021)
The prospective study has been designed to determine some biomarkers in Iraqi female patients withbreast cancer. The current study contained 30 patients whose tissue samples have been collected fromhospitals in Medical City in Baghdad after consent patients themselves and used immunohistochemicaltechnique to determine these markers. The results showed a significant correlation between ER and PR tissuemarkers (Sig = 0.000) and a significant correlation between cyclin E phenotype and cyclin E intensity (Sig =0.001).